Zimbabwean Indigenisation and the Shadow Economy of Cinematic Production. Issue 4 (2nd October 2018) - Ureke, Oswelled
ABSTRACT: In recent years, Zimbabwe has suffered a political and economic crisis, which has generated impulses that have traumatised the country's film industry, among many other sectors. Resultantly, Zimbabwe's cinematic context of production has been reimagined and reconfigured in recent years. The southern African country's ruling elite, during former president Robert Mugabe's tenure, championed controversial policies of indigenisation in economic sectors, partly as a way of countering external economic and political hostilities. This article explores how the Zimbabwean film economy has responded to postcolonial indigenisation impulses and how the production context has developed parallel to or in tandem with this reality. It teases out the challenges and prospects posed by impulses of indigenisation in Zimbabwe to the country's fledgling film production industry by analysing the video-film production value chain post-2000, when the indigenisation agenda emerged and was consolidated. Informed by the theorisation of the shadow economies of cinema, the study employed in-depth interviews to collect data from purposively selected Zimbabwean filmmakers and policymakers. Thematic analysis was used to analyse this data. The study shows that indigenisation has been a pragmatic response to the economic trauma facing the film industry, although it has, in turn, sent out its own traumatic impulses that continue to affect the industry's structure and aesthetic.